Change of Cr, Co, and V concentrations in forest trees by species, organ, and soil depth - Ramazan Erdem (BioResources, 2023)
Heavy metal pollution is one of the most important environmental problems threatening living organisms and environmental health. Thus, there is much research interest in monitoring and reducing heavy metal pollution. Plants’ potential to accumulate heavy metals in various organs differs greatly. Therefore, it is necessary to determine the most suitable species and organs first and acquire knowledge of the subjects such as the transfer of heavy metals within plants and their particular intake into plants. This study investigated Cr, Co, and V, which are among the most important and dangerous heavy metals, and are listed in the primary pollutant list of the Agency for Toxic Substances and Disease Registry. Their concentrations were studied at different depths of soils where Pinus nigra, Pinus sylvestris, Fagus orientalis, and Abies nordmanniana subsp. bornmüelleriana species are grown, in the leaves, cones, wood, bark, and roots. The results showed that the intake of these elements into plant bodies generally occurs through the soil. Additionally, the highest concentrations in both leaves and roots were generally obtained in Fagus orientalis and Abies nordmanniana subsp. bornmüelleriana species. It can be stated that those species are the most suitable species to monitor and reduce heavy metal pollution.
Keywords: tree roots; phytoremediation; cobalt; vanadium; chromium; heavy metals; TP248.13-248.65; Biotechnology; 15. Life on land; 6. Clean water; 13. Climate action